Balancing Visual Outcome and Systemic Function: A Rare Case of Amantadine Keratopathy in a Patient with Severe Parkinson’s Disease - Shah, Nand (Canadian Journal of Optometry, 2025)
Amantadine is a medication increasingly prescribed for the treatment of Parkinson’s disease with significant side effects including amantadine keratopathy. Amantadine keratopathy is a rare, dose-dependent, and cumulative disease process in which the drug amantadine causes severe corneal edema and subsequent decreased visual acuity. While the keratopathy is usually reversible upon discontinuation of the drug, this report details a unique case where drug termination was not an option, and co-management with the patient’s neurologist was necessary to balance visual outcomes and systemic function. A review of Parkinson’s disease along with the incidence, prevalence, and pathophysiology of amantadine keratopathy are discussed. Clinical considerations such as risk factors and dosing patterns for developing keratopathy from this drug are also presented.